Highlighting Lag-Lagto River: Developing A Promotional Video to Position San Miguel Baggao, Philippines as A Key Tourist Site - Trisha Angelica S. Bacud; Babyjane Casillano; Diana Elizabeth L. Lumabao; Gianne Kyle F. Quilang; Rose Fatima G. Suyu; Belman O. Millan Jr (PROGRAM STUDI PARIWISATA SYARAH, FAKULTAS EKONOMI DAN BISNIS ISLAM, UNIVERSITAS ISLAM NEGERI MATARAM, 2025)
Purpose: This study aims to create a high-quality promotional video to boost the visibility and appeal of the Lag-Lagto River in San Miguel, Baggao, Philippines, as a prime tourist destination. It seeks to fill gaps in marketing and data by producing an engaging visual tool to promote the site effectively. Method: The study used a developmental research design to create a promotional video highlighting the Lag-Lagto River’s beauty and attractions. Insights from local stakeholders were gathered through purposive sampling, with data collected via surveys and observations to evaluate the video’s promotional effectiveness. Result: The study found that the promotional video significantly enhanced the Lag-Lagto River’s visibility and appeal, effectively showcasing its beauty and potential. It also confirmed that digital media is a cost-effective and powerful tool for promoting emerging tourist destinations. Contribution: The study highlights the value of high-quality promotional videos in boosting tourism visibility and engagement. It provides a practical framework for using multimedia and storytelling in tourism marketing, contributing to local economic growth and sustainable tourism development.